HIP-HOP AND THE LIMITS OF POLITICAL ENGAGEMENT IN THE AGE OF OBAMA - Muhammad Beni Saputra (Cakrawala - Jurnal Humaniora, 2019)
Hip hop has the power to be a political force. It has also been successful in mobilizing young people for political activities through organizations and big rappers. Unlike its past where the music genre had a commitment to resist and challenge mainstream politics, the United States presidential election of 2008 changed the tradition from defying politics to actively engaging in it. Obama’s blackness became the impetus to this progressive move for his candidacy was regarded as the most tangible manifestation of a black leader. The political engagement, however,  is limited to the fact that music has been monopolized by few companies and that hip-hop artists often have personal interests when involving in politics.